2022
DOI: 10.1002/clt2.12145
|View full text |Cite
|
Sign up to set email alerts
|

Normalisation of airflow limitation in asthma: Post‐hoc analyses of TRIMARAN and TRIGGER

Abstract: Background In asthma, persistent airflow limitation (PAL) is associated with poorer control, lung function decline and exacerbations. Using post‐hoc analyses we evaluated: the relationship between post‐salbutamol PAL at screening, airflow limitation (AL) during 52 weeks treatment with extrafine beclometasone dipropionate/formoterol fumarate/glycopyrronium (BDP/FF/G) versus BDP/FF and the risk of moderate/severe asthma exacerbations. Methods TRIMARAN and TRIGGER were double‐blind studies comparing BDP/FF/G with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The patients under triple inhaler treatment (open or closed) in the TRIMARAN and TRIGGER studies demonstrated a significant reduction in the rate of moderate and severe exacerbations compared to those on ICS + LABA alone, by 15% and 12%, respectively, with no significant differences between the open and closed treatment combinations [ 30 ]. These reductions, however, showed a significant seasonal variation, as they were greater in winter, when the reduction in the rate of moderate and severe exacerbations with triple inhaler treatment was 20.3% compared to ICS + LABA alone, while in the other seasons of the year the corresponding reductions varied between 8.6% and 12.0% [ 46 ]. Furthermore, patients with higher reversibility in post-bronchodilator forced expiratory volume in 1 s (post-FEV 1 ) (>400 mL) experienced greater exacerbation reduction benefit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients under triple inhaler treatment (open or closed) in the TRIMARAN and TRIGGER studies demonstrated a significant reduction in the rate of moderate and severe exacerbations compared to those on ICS + LABA alone, by 15% and 12%, respectively, with no significant differences between the open and closed treatment combinations [ 30 ]. These reductions, however, showed a significant seasonal variation, as they were greater in winter, when the reduction in the rate of moderate and severe exacerbations with triple inhaler treatment was 20.3% compared to ICS + LABA alone, while in the other seasons of the year the corresponding reductions varied between 8.6% and 12.0% [ 46 ]. Furthermore, patients with higher reversibility in post-bronchodilator forced expiratory volume in 1 s (post-FEV 1 ) (>400 mL) experienced greater exacerbation reduction benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Lung function is another key aspect of asthma, as it might mirror disease control. In contrast to asthma symptoms and exacerbation control, the addition of a LAMA to the dual therapy of ICS + LABA in patients with asthma that remains uncontrolled leads to a clearly beneficial effect on lung function [ 46 ]. For this reason, patients on LAMA + ICS + LABA usually presented with worse lung function during the initial clinical assessment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixed airflow obstruction occurs in up to a third of people with asthma, even in those labeled as “mild asthma.” 3 It can be debilitating and is complex in pathophysiology in which peripheral airway dysfunction is fundamental. 3 , 4 , 5 Although long-acting muscarinic antagonists are particularly beneficial when there is fixed airflow obstruction, 6 , 7 suggesting parallels with smoking-related obstructive disease, treatments that are disease-modifying or curative remain greatly needed. Arguably, the key to finding treatments and managing this major problem will be in the peripheral airways.…”
Section: The Future: Comprehensive Phenotyping Including Peripheral A...mentioning
confidence: 99%